Research on Transmission Error of Hypoid Gear based on Real Tooth Surface - Yimin Mo; Renjie Mo; Qiming Li; Jie Liu; Junjian Yang; Yecai Huang (Jixie chuandong)
Aiming at the inconsistency evaluation standards caused by using the gear designed by theory for simulation and using the gear produced by actual production for roll inspection certificate test，by using the NURBS surface fitting method，the real tooth surface is reconstructed and the construct of the 3D model in CATIA software is carried out. The Abaqus software is used to analyze the error of the hypoid gear transmission of the real tooth surface，and the transmission error of the real tooth surface meshing and the pure theoretical tooth surface meshing is compared，the existence of real tooth surface error and its negative influence on transmission error are verified. Changing the installation error of the gear found that the influence of the shaft angle error，the small wheel installation distance error，the offset distance error and the large wheel installation distance error on the transmission error decreased in turn. The rationality of the real tooth profile simulation model is verified by the rolling machine experiment.